PENGARUH PENERAPAN METODE SAVI (SOMATIK, AUDITORY, VISUAL DAN INTELEKTUAL) TERHADAP HASIL BELAJAR FIQIH SISWA KELAS VII MADRASAH TSANAWIYAH SWASTA AL-HIDAYAH TALANG BAKUNG KOTA JAMBI PROVINSI JAMBI - Ahmad Ridwan; Madyan Madyan; Idhari Subagia; Jainah Febi Wahyuni (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research is motivated by the low student learning outcomes of Fiqh caused by the lack of absorption of students in learning Fiqh, the lack of activity of students and the methods used by teachers in managing learning are still monotonous so that students often feel bored quickly when faced with conventional learning methods. This study aims to determine the effect of the application of the SAVI (Somatic, Auditory, Visual, Intellectual) Method on the Fiqh Learning Outcomes of Class VII Students at Madrasah Tsanawiyah Swasta Al-Hidayah Talang Bakung, Jambi City. This study uses quantitative research methods with a Quasi-Experimental research design with a post control group. The research instrument used was a test sheet consisting of questions. In analyzing descriptive data and parametric statistics used normality test, homogeneity test and hypothesis test (T-Test). Based on the results of research conducted, the average score obtained from classes that do not use the SAVI method is 68.62%, while the average score for classes that use the SAVI method is 79.11%. The results of the calculation of the hypothesis obtained a value of 3.45. This value is higher than Ttable 5% = 1.677. The score shows that the use of this research method is better than those who do not apply the SAVI method (Somatic, Auditory, Visual, Intellectual). Based on the results of this study, the researcher recommends schools or other parties to use the SAVI (Somatic, Auditory, Visual, Intellectual) method in learning fiqh with taharah material.